Assessment of Factors Influencing Consumers’ Preference for African Print Fabrics in Southwest Nigeria - Adeloye, Adebayo Abiodun; Oyinloye, Michael Abiodun; Oladesu, Johnson Olarinde; Kayode, Tope Dare (The Outlook: Journal of English Studies, 2023)
This study examines the factors influencing consumers' preferences for African print fabrics, also known as African prints or Ankara fabrics, which are machine printed wax print designs on textiles. These fabrics hold a significant economic value and are considered premium products in the African textile market. The research specifically focuses on Southwest Nigeria. A survey research design was adopted, utilizing both open-ended and close-ended questionnaires. The study population comprised users of African print fabrics in Southwest Nigeria. To determine the sample size, online sample size calculator was used due to the infinite number of African print fabric users. A total of 384 users were sampled. The collected data was analyzed using descriptive statistical tools, and inferential analysis was conducted using independent sample t-test. The findings indicate that design plays a crucial role in influencing the purchasing decisions of African print fabric users. Based on the results, it is recommended that African print companies prioritize the quality of their designs and consider consumers' preferences, including colour choices and motifs, during the design process.